Analisis Yuridis Tindak Pidana Phishing Berdasarkan UU ITE: Studi Kasus Putusan PN Pekanbaru Nomor 764/Pid.Sus/2022/PN.PBR - Erwin Ibrahim Muchsin; Nurmalia Ihsana (HUMANIORUM, 2026)
Phishing is a form of cybercrime that has developed rapidly along with the increasing use of information technology and electronic systems in modern society. This crime is carried out through manipulation or impersonation to unlawfully obtain personal data or electronic access, which may cause significant losses to victims. This study aims to analyze the legal enforcement of phishing crimes based on Law Number 11 of 2008 on Information and Electronic Transactions as amended by Law Number 19 of 2016, through a case study of the Decision of the Pekanbaru District Court Number 764/Pid.Sus/2022/PN.PBR. The research employs a normative legal research method using a statutory approach and a case approach by examining relevant legislation and the judges’ legal considerations in the decision. The results indicate that the defendant’s actions in the a quo case fulfill the elements of criminal offenses stipulated under the ITE Law, particularly regarding illegal access and misuse of electronic systems. Nevertheless, challenges remain in evidentiary aspects and in interpreting the elements of the offense, which require careful legal reasoning to ensure effective law enforcement and legal certainty in handling phishing crimes. Therefore, strengthening the understanding of law enforcement authorities and developing adaptive regulations are necessary to address the evolving nature of cybercrime.